2021
DOI: 10.1002/andp.202100419
|View full text |Cite
|
Sign up to set email alerts
|

Free Space Realization of the Symmetrical Tunable Auto‐Focusing Lommel Gaussian Vortex Beam

Abstract: An auto-focusing beam with adjustable symmetry is proposed numerically and experimentally. The initial field of the auto-focusing Lommel Gaussian vortex beam (ALoGVB) consists of the Lommel function and the Gaussian term. When the asymmetry factor 𝜺 of the beam approaches zero, the ALoGVB will degenerate into a circular Bessel Gaussian vortex beam (CBGVB). Compared with the CBGVB, the ALoGVB is more diverse. The shape, symmetry, normalized focusing intensity, and focus distance of the ALoGVB can be controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…When 𝜀 = 0.75 exp(i𝜋∕4), comparing Figure 3 a1,b1) with Figure 3 a5,b5, it is clear that there are still two circular breaks inside the main ring of the beam and its symmetry axis is rotated 45 • clockwise. The rotation angle of the axis of symmetry is given by 𝛿 = arg(𝜀), and arg(⋅) represents the argument of the complex number, [19] which indicates that the symmetry of LoTW can be flexibly controlled. The experimental results are in good agreement with the numerical results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When 𝜀 = 0.75 exp(i𝜋∕4), comparing Figure 3 a1,b1) with Figure 3 a5,b5, it is clear that there are still two circular breaks inside the main ring of the beam and its symmetry axis is rotated 45 • clockwise. The rotation angle of the axis of symmetry is given by 𝛿 = arg(𝜀), and arg(⋅) represents the argument of the complex number, [19] which indicates that the symmetry of LoTW can be flexibly controlled. The experimental results are in good agreement with the numerical results.…”
Section: Resultsmentioning
confidence: 99%
“…where 𝜀 is the asymmetry factor, 𝛼 stands for a spatial distribution factor, r 0 is the main ring radius of the beam, n is the topological charge, U n (⋅) denotes Lommel function, which is expressed as [19] U Q(𝜌) is the truncation function, which can be denoted as…”
Section: Methodsmentioning
confidence: 99%
“…Yu et al investigated the detection probability of received OAM modes in anisotropic oceanic turbulence with Lommel-Gaussian beam and showed that small asymmetric parameter and topological charge benefit information transmission [38]. Tu et al proposed autofocusing Lommel-Gaussian beam and showed that the shape, symmetry and focusing distance of the beam can be well controlled by adjusting the topological charge and asymmetry factor [39]. Wang et al analyzed the capacity of UWOC links with the localized Lommel-Gaussian beams and demonstrated that the system capacity uplifts with the increment of the OAM channel number [40].…”
Section: Introductionmentioning
confidence: 99%